Maternal Mental Health and Mindfulness - Wardi-Zonna, Katherine; Wardi, Anissa (Journal of the Motherhood Initiative for Research and Community Involvement, 2020)
Mental health problems result in disease and disability (Afifi 385). When looking at the data across cultures, women are more likely to report mental health symptoms, access available supports, and receive treatment for mental health disorders (Lesesne and Kennedy 755). Research on maternal health has suggested that “the burden of mental health disorders peak in the child bearing and midlife periods” (Lesesne and Kennedy 756). Biology is often implicated in this presumed psychological vulnerability, given that throughout a woman’s life, she experiences pronounced hormone-driven cycles, including menstruation, pregnancy, a postpartum period, and menopause. However, even after exhaustive studies exploring a number of sex-related variables, there is a lack of consensus regarding the significance hormones have in influencing women’s mental health challenges (Hendrick et al. 93; Schiller et al. 49). Some scholars contend that the focus on biology and hormones are an easy way to discount the negative experiences that disproportionately affect girls and women. Discrimination, poverty, sexism, abuse, exploitation, and caregiving burdens work to undermine women’s mental health. Women’s mental health should, therefore, be understood by evaluating all aspects of women’s lived experiences—physical, sociocultural, economic, and interpersonal. Informed by the diathesis-stress model, this article reconsiders the social, political, and economic stress that adversely affects women’s wellbeing. Specifically, this article posits that Buddhist-derived interventions, such as mindfulness, can fortify and empower women. Evidence from neurobiology provides a meaningful framework supporting this approach to health and wellness.